Nursing Care of Children Undergoing Congenital Heart Surgery - เหล่าพาณิชย์เจริญ, ปภาวดี (Journal of The Royal Thai Army Nurses, 2018)
Congenital Heart Disease is a disease of the infant developmental abnormalities in the fetus and death or disability. This type of congenital heart disease can be treated with surgery to correct the defect, reduce child mortality. The treatment needs to be treated by specialist surgeon (Cardiovascular Thoracic surgeon) is to consider whether or not to have surgery. Choose when and how the individual child so that the effect of the surgery is safe and complications minimal under the collaboration of multidisciplinary. The operative nurses are responsible for not only preparing equipment for surgery, but also providing care during preoperative, intraoperative and postoperative care to promote safety and comfort of children. Surgical correction of congenital heart that causes the heart to stop beating requires materials in which the heart stops was “Cardioplegia Needle’s guard” will be applied for surgical technique